Earthworms in natural grasslands and agropastoral systems in the Brazilian Pampa - Gillanders, Stephen M.g.; Podgaiski, Luciana R.; Overbeck, Gerhard E.; Santos, Alessandra; Winck, Bruna; Brown, George G.; Bartz, Marie L.c. (Zootaxa, 2023)
In this study, we sampled grazed natural grassland and agropastoral systems in two regions (Alegrete and Aceguá) in the highly diverse Brazilian Pampa region which is undergoing significant change in land use cover. By hand sorting the soil, a total of five species were found, belonging to the families Glossoscolecidae (Glossoscolex sp.50 and Glossoscolex sp.51), Ocnerodrilidae (Kerriona sp.6 and Eukerria sp.3), and Lumbricidae (Aporrectodea trapezoides). The former four were identified as native—new to science—and the latter as exotic. Differences were observed in both earthworm species richness and abundance between regions and land-use systems, likely due to environmental conditions and agricultural practices, respectively. Agropastoral systems had higher abundance and species richness than natural grasslands, though these differences varied by location. This suggests that conversion from natural grassland to agropastoral systems can maintain native earthworms and, possibly, enhance ecosystem services. However, an exotic species was found in high abundance at one agropastoral site. These results highlight the need for additional biodiversity studies on earthworms in the Brazilian Pampa and for research on the impacts of land use changes in this region.